Homegrown Transplants: Procedural Borrowing in the New Ontario Class Proceedings Act - Kalajdzic, Jasminka; Zimmerman, Adam (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2024)
The most controversial of the recent amendments to Ontario’s Class Proceedings Act is the addition of two requirements to the certification test: to meet the preferable procedure criterion, s. 5(1.1) requires that common issues in the litigation must now “predominate” over individual issues, and a class action must be “superior” to all other forms of resolution. The importance of the interpretation of Ontario’s new certification test to the continued viability of class actions in the province merits a thorough and rigorous analysis of s. 5(1.1). The language of predominance and superiority is strikingly similar to requirements that have long applied to US class actions for monetary damages. As courts in Ontario begin to grapple with the new predominance and superiority requirements, however, the authors caution against turning to American jurisprudence for guidance. Several important structural differences between the Ontario and American class action regimes, as well as different constitutional considerations and a variety of approaches within US case law diminish its utility. Instead, the authors examine the history and language of the amendments to propose an interpretation of the predominance and superiority requirements that is informed by Canada’s own procedural and constitutional framework and that avoids the pitfalls of legal transplants.